Microglial C/EBPβ-Fcgr1 regulatory axis blocking inhibits microglial pyroptosis and improves neurological recovery - Jing Li; Yubing Yang; Chenguang Zhao; Jinghao Zhao; Xiaohui Wang; Shengshou Ye; Dong Wang; Chengdong Zhou; Jie Li; Shuang Wang; Ke Li; Chunmiao Liu; et al. (Journal of Neuroinflammation)
Abstract CAAT/Enhancer Binding Protein β (C/EBPβ) is associated with inflammatory responses in neurodegenerative pathologies, particularly in the brain. However, the regulatory role of C/EBPβ in spinal cord injury and its impact on neurological recovery remain unknown. In this study, we observed significant upregulation of C/EBPβ in microglia after spinal cord injury in mice and was associated with neuroinflammation. Knocking down C/EBPβ in the spinal cord attenuated microglia pyroptosis, reduced the production of proinflammatory cytokines, and inhibited neuronal apoptosis. Mechanistically, C/EBPβ promoted the transcription of Fcgr1, which was involved in activating microglia pyroptosis. In both in-vivo and in-vitro experiments, knocking down Cebpb or Fcgr1, or the pyroptosis inhibitor VX765 inhibited neuronal apoptosis and improved neurological recovery in mice. These findings indicate that C/EBPβ functions as a key regulator that participates in the microglia pyroptosis-mediated neuroinflammation by activating Fcgr1 transcription.